2017
DOI: 10.3280/efe2017-001006
|View full text |Cite
|
Sign up to set email alerts
|

Business model experimentation for circularity: Driving sustainability in a large international clothing retailer

Abstract: Business model experimentation for sustainability is an intentional and systematic approach to identify, test and learn about value creation strategies that could be adopted by a business in response to current unsustainable trajectories. For businesses such as large clothing retailers the need to alter course is acute as pressure builds from economic, environmental and social angles. The circular economy concept provides a potential powerful lever for change. To date, however, scant research has been conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 69 publications
4
81
0
2
Order By: Relevance
“…For instance, a number of business model visualization and mapping tools have been suggested that build on the Business Model Canvas by Osterwalder and Pigneur and emphasize the notion of 'value creation' [23,30,72,[77][78][79]. Popular innovation approaches, such as effectuation (learning from entrepreneurial practice) [80] and lean start-up (focusing on trialing new ideas in practice in a fast and iterative way) [73], have been used as building blocks for recent approaches to CBMI [81,82]. Many other tool types that focus on ideation for CBMs are also emerging, such as serious games [83,84], case databases [85] and typologies [61].…”
Section: Tools For Circular Business Model Innovation: Gaps and Oppormentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a number of business model visualization and mapping tools have been suggested that build on the Business Model Canvas by Osterwalder and Pigneur and emphasize the notion of 'value creation' [23,30,72,[77][78][79]. Popular innovation approaches, such as effectuation (learning from entrepreneurial practice) [80] and lean start-up (focusing on trialing new ideas in practice in a fast and iterative way) [73], have been used as building blocks for recent approaches to CBMI [81,82]. Many other tool types that focus on ideation for CBMs are also emerging, such as serious games [83,84], case databases [85] and typologies [61].…”
Section: Tools For Circular Business Model Innovation: Gaps and Oppormentioning
confidence: 99%
“…The (C)BMI process is highly iterative, and as mentioned before, researchers have tried to find different 'entry-points' for tools in the process. In this paper, we adopted the generic phases of 'ideation and design', 'implement and test' and 'evaluate and improve' [40,81,82]. A limitation of this approach is that in practice, the (C)BMI process in companies may follow different phases or may take place in a more ad-hoc manner.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability to effect changes in traditional BM, which may not be aligned with the SD concept, has recently been acknowledged as a fundamental approach to achieving sustainability [63]. According Sustainability 2020, 12, 2337 6 of 34 to Bocken et al [64], there is a close connection between sustainable BMI and experimentation. The latter refers to the process of seeking innovations that can result in sustainable BMs.…”
Section: Bmi Mechanisms and Sustainabilitymentioning
confidence: 99%
“…And as in the example of the football pitch, we need various players in the market to experiment together to create this movement-thus creating an ecosystem for innovation. Sustainable business requires innovation on a large scale, but a necessary step is to test ideas in new and existing markets (Bocken et al 2017). This underscores the need for controlled experimentation.…”
Section: Changes Big and Smallmentioning
confidence: 99%